Influenza A Virus Weakens the Immune Response of Mice to Toxoplasma gondii, Thereby Aggravating T. gondii Infection - Junpeng Chen; Xiaoli Wang; Jinxuan Li; Lingyu Sun; Xiao Chen; Ziyu Chu; Zhenzhao Zhang; Hongxia Wu; Xiaomin Zhao; Hongmei Li; Xiao Zhang (Veterinary Sciences, 2023)
This study aimed to investigate the relationship between the T. gondii type II strain (Pru) and respiratory viral infections, specifically focusing on the co-infection with PR8 (influenza A/Puerto Rico/8/34). In this study, we found that the number of T. gondii (Pru) in the lungs of co-infected mice was significantly higher and lesions were more severe than those in the group infected with T. gondii (Pru) alone, whereas IAV (influenza A virus) copy numbers of co-infected and PR8 alone infected groups were negligible, suggesting that infection with IAV increased the pathogenicity of T. gondii (Pru) in mice. The invasion and proliferation assays demonstrated no significant effect of co-infection on T. gondii (Pru) infection or replication in vitro. To further explore the factors causing the altered pathogenicity of T. gondii (Pru) caused by co-infection, we found that decreased expression levels of IL-1β, IL-6, and IL-12 in the co-infected group were associated with the early immune responses against T. gondii (Pru), which affected the division of T. gondii (Pru). Moreover, the significant decrease in the CD4+/CD8+ ratio indicated a weakened long-term immune killing ability of the host against T. gondii (Pru) following IAV infection. In conclusion, a T. gondii type II strain (Pru) could not be properly cleared by the host immune system after IAV infection, resulting in toxoplasmosis and even death in mice.